Problems of media programs of teacher training institutions in the Greater Manila area - Silachan, Wamalyao 1941-
This study surveyed the problems that beset the educational media programs of the teacher training colleges in the greater Manila Area. The suggested solutions to these problems were also solicited through the use of a questionnaire.